Impact of Virtual Classes on Secondary Level Students in Public Schools in Nepal - Acharya, Milan (Innovative Research Journal, 2024)
Information and Communication Technology plays a major function in online/virtual classes. This study explores the impact, effectiveness, and challenges of virtual classes among secondary school students and teachers in Kirtipur Municipality. The research involved 20 secondary level teachers and 80 students from grades nine. Using a quantitative approach, data were collected through survey questionnaires. Simple random sampling was used to select the participants. The findings revealed that technical devices like smartphones, laptops, and desktop were commonly used for online classes. Virtual classes proved to be effective during the pandemic but require better resources, skills, and strategies to maximize their potential in future teaching and learning practices. However, participation among students remained l ow despite access to devices. Teachers and students faced challenges in adopting to online classes due to lack of technical skills. The study recommends training programs for teachers and students to improve their ability to use technology effectively. It also highlights the need to integrate online teaching during critical times and emergencies.